Development of Monopoly as a Game-Based Learning Media on Pancasila Education Material My Country Indonesia For Grade IV Elementary Students - Asnafiyah, Asnafiyah; Salsabila, Syalita Hilda (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2024)
This study aims to determine the characteristics of monopoly media developed and to obtain game-based monopoly media that are feasible to use according to experts and prospective users' responses to monopoly media. This type of research is Research and Development (R&D) with the 4D model which consists of four stages, namely Define, Design, Development, and Disseminate. Data collection instruments came from interviews, observations, and questionnaires. The data obtained in this study are qualitative and quantitative data. The respondents in this study were grade IV students of SD Muhammadiyah Suronatan Yogyakarta with a total of 20 people. The results showed the characteristics of game-based monopoly learning media on Pancasila Education material My Country Indonesia consists of components made using Ivory 230gsm paper and ArtPaper 150gsm. The game board measures 30cm x 30cm, the cards are made with a size of 3.5cm x 6.5cm, the storage box measures 34cm x 17cm which is equipped with a locking box to protect the contents of the game components, as well as an A5 guidebook and answer key. The results of the developed product can help students understand the material in a more fun way. The media is classified as very feasible with a score of 4.7 from material experts and media experts, classified in the feasible category with a score of 4.3 from linguists, and classified in the very feasible category with a score of 4.9 from practitioner responses. The developed media received a readability response from prospective users with an average score of 8.15 and a percentage of 91% from 20 students.